STUDI ETNOBOTANI TUMBUHAN DAUN GATAL DI KECAMATAN KWAMKILAMA KABUPATEN MIMIKA - Samuel A. Mom; Martina A. Langi; Reynold P. Kainde; Wawan Nurmawan (COCOS, 2015)
ABSTRACT The objective of this research was to identify the plant species traditionally called as Daun Gatal at Kwamkilama, the district of Mimika. Along with that, the traditional use of Daun Gatal was also studied. Method used in this study was direct observation, interview, and questionnaire. Data were collected gradually that was from heads of village to people recommended by them and so forth. Results show that there are three species (Laportea decumana, Laportea interupta, and Dendrocnide peltata) all belong to family Urticaceae. Furthermore, traditional use of these species were for medicines (of many diseases), stamina booster, hunting, and ethnical coustum.Key words: Daun Gatal plant, Papua, Laportea, Dendrocnide.